Desempeño organizacional y satisfacción laboral de las principales asociaciones de artesanos en Iquitos 2024 - Del Aguila Gonzales, Bianca Fiorella (2025)
The purpose of this study was to determine the relationship between organizational performance and job satisfaction in the main artisan associations in Iquitos 2024. It was a pure, relational, non-experimental, transectional design, population composed of 114 artisans belonging to the most representative associations, the sample being 88 artisans from the main artisans' associations. The instrument was validated by means of expert judgment and the reliability of the data collection was checked. The SPSS v25 software was used to analyze and interpret the data, obtaining the following results: organizational performance was inefficient in 65.9%; efficient 23.9%; inefficient 10.2%. Job satisfaction was low in 68%; regular 31.8%. Conclusions: Organizational performance is not related to job satisfaction in the main artisan associations in Iquitos (X2=0.048; gl=2; p=0.976).